IMPLEMENTATION OF ISLAMIC BUSINESS MANAGEMENT IN BUDIMAN SUPERMARKET SAWAHAN PADANG CITY - Sabiruddin, Sabiruddin; Fransiska, Arina; Basra, Sri Meiweni; Yunus, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2024)
Budiman Supermarket Sawahan, Padang City, upholds Islamic values based on Sharia or Islam. The problem in this research is how to implement Islamic Business Management in Budiman Supermarket, Padang City. The research aims to determine how Islamic Business Management is implemented in the aforementioned Supermarket. The research method used was a qualitative method with a descriptive approach. The research data sources are the Managers, employees, and consumers of Budiman Supermarket Sawahan. Supporting data comes from books and documents. Data collection techniques are through observation, interviews, and documentation. Data processing employs data reduction, presentation, analysis, and conclusions. The research results show that the implementation of business management at Budiman Supermarket, Padang City, can be seen from several aspects: first, business management, namely the marketing aspect, management activities based on functions that try to identify consumer needs and how to realize consumer desires—second, implementing a mixed strategy of product, price, and promotion. Furthermore, the implementation of Islamic Business Management in Budiman Supermarket can be seen from Islamic business marketing management, which has three concepts: trust, building, and creating trust. Second is quality service, namely the services provided, and third is responsibility or trust.